Diagnostic approach and treatment of Zenker’s diverticulum - Ordaz, David Eduardo Torres; Montes, Jose Ignacio Diego Perez; Lugo, Leonel Lozano; Mauricio , Leonel lturbide (International Journal of Research in Medical Sciences, 2024)
Pharyngoesophageal diverticulum have many subtypes, Zenker’s diverticulum being the most common of them. Accounting from 70 to 75% of all esophageal diverticula. The 50% of these occur between the seventh and eighth decade of life. The most common symptom is dysphagia. The predominant symptom of ZD is dysphagia and the most serious is pulmonary aspiration. A 68-year-old female attended a general surgery consultation with progressive dysphagia, weight loss, regurgitation and halitosis. Laboratory studies showed normal, while the upper gastrointestinal series (UGI) showed stasis in the upper part of the esophagus. Digestive panendoscopy revealed Zenker’s diverticulum, diverticulectomy and cricopharyngeal myotomy were performed. Zenker’s diverticulum is diagnosed through radiological studies and endoscopy. Surgical management is necessary due to the list of complications if left untreated.